دور الزوايا الرحمانية في الحفاظ على اللغة العربية أثناء الفترة الاستعمارية -زاوية سيدي سالم بالوادي أنموذجا- - غدير إبراهيم, خيرة; سواكر, كريمة (University of Eloued جامعة الوادي, 2020)
- تعتبر هذه الدراسة من بين الدراسات التي بحثت في تاريخ ظهور الطرق الصوفية في فترة الإحتلال الفرنسي للجزائر، وخاصة الطريقة الرحمانية التي بذلت جهدا كبيرا لمقاومة الاستعمار سواء بالسلاح أو بالعلم وتنمية الفكر، فهذه الطريقة بمختلف مراكزها المتواجدة عبر كامل التراب الجزائري وبالأخص في الجنوب الشرقي، فقد عملت جاهدة لتنوير فكر المجتمع الجزائري وحماية مقوماته من هجوم المستعمر، ومحاولته لفرنسة هذا الشعب المتمسك بهويته، ودينه،ولغته، فكان هذا أحد أهداف فرنسا في ذلك الوقت ،ولكن بفضل هذه الطريقة وغيرها من الطرق التي اهتمت بهذا الجانب لم يتمكن المستعمر من بلوغ أهدافه ، لذا فهذه الطريقة تعتبر من أهم العوامل والأسباب التي جعلت المجتمع الجزائري بقي محافظا على دينه ولغته في ظروف صعبة جدا كالظروف التي عاشها في تلك الفترة .This study is considered among the studies that examined the history of the emergence of the Sufi orders during the period of the French occupation of Algeria, especially the Rahmani order, which made a great effort to resist colonialism, whether with weapons or science and the development of thought, so this method, with its various centers throughout the entire Algerian soil, especially in the southeast, I worked hard to enlighten the thought of Algerian society and protect its components from the attack of the colonizer, and its attempt to Frenchize this people who cling to their identity, religion and language. This was one of France's goals at that time, but thanks to this method and other methods that paid attention to this aspect, the colonizer could not achieve its goals. Therefore, this method is considered one of the most important factors and reasons that made Algerian society preserve its religion and language in very difficult circumstances, such as the circumstances it lived during that period
مذكرة ماستر تخصص دعوة واعلام
Keywords: الزوية الرحمانية - اللغة العربية – الاستعمار - سيدي سالم; Zawia Rahmani - Arabic Language - Colonialism - Sidi Salem